HYPOGLYCEMIC ACTIVITY OF HYDRO-ALCOHOLIC EXTRACT OF CALYCOPTERIS FLORIBUNDA INDUCED BY STREPTOZOTOCIN IN RATS (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
The present investigation was carried out to study the hypoglycemic effects of the hydro-alcoholic (70:30) extract of Calycopteris floribunda, in normal and streptozotocin induced diabetic model. Calycopteris floribunda, are reported to have medicinal and traditional values including hypoglycemic properties. Decreased blood glucose level of the test animals shows that the extract exhibit significant hypoglycemic activity when compared to diabetic control group, effect of various doses (100, 200 mg/kg, p.o) extract was studied on streptozotocin induced both diabetic and non diabetic rats. The results also indicated the dose dependent effect. The hypoglycemic activity produced by the extract may be due to increased uptake of glucose at the tissue level or by an increase in pancreatic beta cell function or due to inhibition of intestinal absorption of glucose. The present study supports the use of this herbal drug as hypoglycemic. The reduction in the glucose level in induced diabetic rats proved that Calycopteris floribunda having the hypoglycemic activity.